2004
DOI: 10.2223/jped.1227
|View full text |Cite
|
Sign up to set email alerts
|

Feeding habits of breastfed and non-breastfed children up to 1 year old

Abstract: Breastfed children had healthier habits than non-breastfed children in terms of the introduction of complementary foods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…The majority of the children assessed were being breast-fed, in agreement with the findings of the research of Vieira et al 13 into 2319 breastfed infants of less than 12 months of age assessed on the national vaccination day when a frequency of 69.2% of them was found to be being breast-fed. Another research project found lower results, 50% of the children assessed of from 6 to 24 months of age attending a family health program in Acrelândia-Acre were found to be being breast-fed¹.…”
Section: Discussionsupporting
confidence: 88%
“…The majority of the children assessed were being breast-fed, in agreement with the findings of the research of Vieira et al 13 into 2319 breastfed infants of less than 12 months of age assessed on the national vaccination day when a frequency of 69.2% of them was found to be being breast-fed. Another research project found lower results, 50% of the children assessed of from 6 to 24 months of age attending a family health program in Acrelândia-Acre were found to be being breast-fed¹.…”
Section: Discussionsupporting
confidence: 88%
“…The same situation has been observed in other national studies (7)(8)(9)(10) , indicating that this is not a local problem.…”
Section: Discussionsupporting
confidence: 87%
“…A comparison between children of less than four months old in this study and children of the same age from a city in the Northeast of Brazil (9) shows that the situation is a bit better in Botucatu: lower prevalence levels of juice (8.4% and 5.6%), soup (5.3% and 2.4%) and home-made food (2.1% and 0.5%), despite similar tea consumption levels (31.8%…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…This calculation took into consideration the number of live births in the municipality in 2003 (10,177), the proportion of children under EBF at 6 months of age reported in a previous study (38.5%) [22] a significance level of 5%, a test power of 90%, and a difference in the outcome of at least 5%, using finite population correction.…”
Section: Methodsmentioning
confidence: 99%